The Impact of Subjective Interoceptive Accuracy on Opinion Change: How Exposure to Opposing Views Influences Perceptions of Events - Huang, Ke (International Journal of Social Sciences and Public Administration, 2025)
This research examines the connection between subjective interoceptive accuracy and the tendency to maintain or alter opinions when individuals were confronted with opposing views. We proposed that individuals exhibiting higher interoceptive accuracy would be less inclined to change their opinions. Surprisingly, our findings did not reveal a significant association between interoceptive accuracy and the extent of opinion change. Notably, however, we identified a moderate association between an increased sensitivity to internal bodily signals-as indexed by the Noticing subscale of the Multidimensional Assessment of Interoceptive Awareness (MAIA-N)-and a higher likelihood of opinion change.  This observation implies that individuals who are more attuned to their internal bodily signals might also be more adaptable in revising their perspectives when exposed to contradictory viewpoints. Overall, these results enhance our understanding of interoceptive accuracy and attitude shifting, highlighting the intricate interplay between bodily sensations and higher-order cognitive processes.